Rebellions and peripheries in the cuneiform world - Richardson, Seth Francis Corning (American oriental series, 2010)
Writing rebellion back into the record : a methodologies toolkit / Seth Richardson -- Rebellions and peripheries in Sumerian royal literature / Nicole Brisch -- Preventing rebellion through the creation of symbolic ties of kinship in Syria and Mesopotamia during the second millennium B.C. / Amanda H. Podany -- The law and politics of rebellion in the late Bronze Age / Raymond Westbrook -- Kings of Tabal : politics, competition, and conflict in a contested periphery / Sarah C. Melville